Chronic Fever with Severe Weakness - A Case Report - Akther, Rabeya; Jesmin, Humayra (Journal of Dhaka Medical College, 2017)
Adult onset Stills disease (AOSD) is a rare systemic inflammatory disease of unknown etiology and pathogenesis that presents in 5 to 10% of patients as fever of unknown origin (FUO) accompanied by systemic manifestations. We report an interesting case of a 63-year-old Bangladeshi male who presented with one-month duration of FUO along with, severe weakness, oral thrush, high WBC count, low RBC count and low hemoglobin concentration. After extensive workup, potential differential diagnoses were ruled out and the patient was diagnosed with AOSD based on the Yamaguchi criteria. The case history, incidence, pathogenesis, clinical manifestations, differential diagnoses, diagnostic workup, treatment modalities, and prognosis of AOSD are discussed in this case report. J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 142-147